Legal Status Typology of Waqf Nazhir and Challenges to Registration with the Indonesian Waqf Board: Insights from Aceh and North Sumatra - Adan, Hasanuddin Yusuf; Jalil, Husni; Damanhuri, Damanhuri; Musa, Armiadi; Bakri, Nurdin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
The implementation of the nazhir registration requirement under Article 14 of Law Number 41 of 2004 on Waqf continues to reveal a gap between legal norms and practice. Although every nazhir is legally required to be registered with the Minister of Religious Affairs and the Indonesian Waqf Board (BWI), in practice many are registered only with the Office of Religious Affairs (KUA), while others remain unregistered with both institutions. Previous studies have primarily examined waqf governance, whereas research developing a typology of the legal status of nazhir based on registration practices remains limited. This study aims to formulate a legal status typology of waqf nazhir and identify the factors hindering registration with the Indonesian Waqf Board. Employing a qualitative socio-legal approach, data were collected through in-depth interviews, observation, and document analysis and were analyzed thematically. The findings identify three legal status typologies of waqf nazhir: formal, registered with both the KUA and BWI, semi-formal, registered with the KUA but not with BWI; and informal, registered with neither the KUA nor BWI. The study further reveals that overlapping institutional authority, weak inter-agency coordination, limited legal awareness among nazhir, and the institutional and budgetary constraints of BWI constitute the main barriers to registration. This study contributes by proposing a legal status typology of waqf nazhir as a conceptual framework for understanding the implementation gap in waqf law and underscores the need to strengthen institutional coordination, harmonize regulations, and develop a digital registration system to enhance legal certainty and the effectiveness of waqf governance in Indonesia.